Listeria monocytogenes meningitis in immunocompetent and healthy children: a case report and a review of the literature - Massimo Luca Castellazzi; Paola Marchisio; Samantha Bosis (BMC, 2018)
Abstract Background Listeria monocytogenes is a gram-positive bacteria generally transmitted to humans through ingestion of contaminated food. It typically infects high risk subjects, such as pregnant women, neonates, the elderly and immunocompromised patients. Listeria meningitis is rarely reported in previously healthy children with no immunological disorders. However, it can be aggressive in such subjects and is associated with a high mortality rate. Prompt diagnosis is essential so that adequate antibiotic treatment can be started and the best outcome achieved. Case presentation We report the case of a previously healthy 16-month-old child with Listeria meningitis who was successfully treated with intravenous ampicillin and gentamicin without any sequelae. Conclusions Although Listeria meningitis is rare in previously healthy immunocompetent children, it must be considered, especially in children who do not improve with first-line antibiotic treatment. A review of the literature published since 1996 has been performed, to provide a general overview on this topic.